1975
DOI: 10.1128/jb.122.2.691-694.1975
|View full text |Cite
|
Sign up to set email alerts
|

Structural similarity of the membrane envelopes of rhizobial bacteroids and the host plasma membrane as revealed by freeze-fracturing

Abstract: The freeze-fracture technique was used to study the host plasma membrane and the membrane envelope of bacteroids in rhizobial root nodules of three host-rhizobium combinations. In all three combinations studied, the membrane envelopes of bacteroids are structurally similar to their host plasma membrane. However, the membrane appears to be reversed, because the number and arrangement of particles in the outer fractured face (face A, concave) and in the inner fractured face (face B, convex) of the host plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Biochemical data (Table IV) suggest that the membrane envelope proteins are synthesized in the host cell cytoplasm. These results, along with earlier observations (5,14,15,35,38,39), confirm that the membrane envelope enclosing the bacteroids originates from plasma membrane of the host and show that most of the known characteristics of the plasma membrane are retained. An extracellular compartment is formed for Rhizobium to develop an "intracellular symbiosis.…”
Section: Origin and Biosynthesis Of The Membrane Envelopesupporting
confidence: 84%
See 2 more Smart Citations
“…Biochemical data (Table IV) suggest that the membrane envelope proteins are synthesized in the host cell cytoplasm. These results, along with earlier observations (5,14,15,35,38,39), confirm that the membrane envelope enclosing the bacteroids originates from plasma membrane of the host and show that most of the known characteristics of the plasma membrane are retained. An extracellular compartment is formed for Rhizobium to develop an "intracellular symbiosis.…”
Section: Origin and Biosynthesis Of The Membrane Envelopesupporting
confidence: 84%
“…These membranes are also sensitive to nonionic detergent (NP-40) both in vitro and in vivo, while bacterial membranes are not. Similarity of these membranes was further borne out by the recent study of Tu (39) showing similar freeze-fracture face particle decoration on these membranes. Analysis of membrane envelope proteins showed a close similarity with the plasma membrane of uninfected cells.…”
Section: Origin and Biosynthesis Of The Membrane Envelopesupporting
confidence: 59%
See 1 more Smart Citation
“…Firstly, several authors have found that the PBM, ITM and plasma membrane all stain with the plasma membrane-specific stain, phosphotungstic acid, whereas other cell membranes do not (Robertson et al 1978b, Roth and Stacy 1989a, Verma et al 1978. Secondly, freeze fracture studies of the PBM and plasma membrane from newly infected nodule cells of soybean, alfalfa and clover have revealed a striking similarity between the particle profiles of the surfaces of the two membranes (Tu 1975). And lastly, antibody studies have shown similarities in the epitopes present on the PBM and plasma membrane throughout PBM development (Perotto et al 1991(Perotto et al , 1995, see further discussion later).…”
Section: Origin Of the Pbmmentioning
confidence: 99%
“…Some authors put forward a route via plasmamembrane, i.e. a membrane recycling (Tu, 1975;Verma et al, 1978;Blumwald et al, 1985), while others propose a more direct membrane flow from ER and Golgi to the peribacteroid membrane (Robertson et al, 1978;Mellor et al, 1984;Mellor and Werner, 1987). We have analysed the fatty acid composition of different nodule-derived membrane systems to contribute further information to this controversy.…”
Section: Introductionmentioning
confidence: 99%